Myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease: practical considerations. Issue 3 (8th December 2018) - Juryńczyk, Maciej; Jacob, Anu; Fujihara, Kazuo; Palace, Jacqueline
Abstract : The field of central nervous system (CNS) inflammatory diseases has recently broadened to include a new condition associated with pathogenic serum antibodies against myelin oligodendrocyte glycoprotein (MOG). This is distinct from multiple sclerosis (MS) and aquaporin-4 (AQP4) antibody neuromyelitis optica spectrum disorders (NMOSD). MOG antibody-associated disease phenotypes are varied and range from classical neuromyelitis optica to acute demyelinating encephalomyelitis and cortical encephalitis. The diagnosis depends on using a reliable, specific and sensitive assay of the antibody. Clinical and imaging features of MOG-associated syndromes overlap with AQP4 antibody NMOSD but can be usually distinguished from MS: in particular, the silent lesions typical of MS that progressively increase lesion volume are rare in MOG antibody disease. The disease can relapse but medium-term immunosuppression appears to be protective. Permanent disability, particularly severe ambulatory and visual disability, is less frequent than in AQP4 antibody NMOSD and usually results from the onset attack. However, sphincter and sexual dysfunction after a transverse myelitis is common. Here we review the practical aspects of diagnosing and managing a patient with MOG antibody-associated disease.